The 'outcry' of the dissected woman in Judges 19-21 : embodiment of a society - Coetzee, Johan (Old Testament essays, 2002)
Body and voice are not categories read into a text but categories in which a text announces itself. This investigation concentrates on these two categories in an effort to shed more light on the literary embodiment of both gender bodies (women and men) and societal bodies (socio-political) functioning in Judges 19-21.